A Cave As A Third Space In Tom Schulman’s Play Dead Poets Society; Practical Inspiration For Teachers - Ariadi, Eka Sugeng (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2019)
Literacy is not a matter of talking and discussing the improvement of reading and writing skills, yet more than that, it is extending as a kind of social practice which involving people’s mundane life to generate specific and unique products of each person. Luckily, literacy can be a put in other subjects; literature and education. In this paper, the notion of third space in literacy is applied as the tool to analyze the role of a cave in Tom Schulman’s play Dead Poets Society, which then influencing a group of Welton Academy students’ awareness of their personal identities, their own cognition and their knowledge needed. To examine the students' movements in connecting three spaces; home, school, and cave, the researcher uses the Knowledge and Cognitive Process dimension, which is retrieved from Bloom’s taxonomy revision as proposed by Krathwohl (2002). The result confirms that the role of a cave, as third space, assists much the students to seek their own voices and identities, and definitely rises their confidence, creativities, and innovations for better transformation. Keywords: Third space, Literacy, Literature, Teaching